DEEP-South: Automated Observation Scheduling, Data Reduction and Analysis Software Subsystem. Issue Volume 10:Issue S318(2015) (1st March 2016) - Yim, Hong-Suh; Kim, Myung-Jin; Bae, Young-Ho; Moon, Hong-Kyu; Choi, Young-Jun; Roh, Dong-Goo; Park, Jintae; Moon, Bora; ,
Abstract: We started 'DEep Ecliptic Patrol of the Southern sky' (DEEP-South, DS) (Moon et al .2015 ) in late 2012, and conducted test runs with the first Korea Microlensing Telescope Network (KMTNet) (Park et al .2012 ), a 1.6 m telescope with 18k x 18k CCD stationed at CTIO in early 2015. While the primary objective of DEEP-South is the physical characterization of small Solar System bodies, it is also expected to discover a large number of such bodies, many of them previously unknown. An automated observation scheduling, data reduction and analysis software subsystem called 'DEEP-South Scheduling and Data reduction System' (DS SDS) is thus being designed and implemented to enable observation planning, data reduction and analysis with minimal human intervention.